Ted & me : a baseball card adventure - Gutman, Dan (Gutman, Dan. Baseball card adventures., 2012)
When Stosh travels back in time to 1941 in hopes of preventing the Japanese attack on Pearl Harbor that brought the United States into World War II, he meets Ted Williams, one of the greatest hitters in baseball history. Includes notes about Williams' life and career.